Modeling, Computing and Data Handling Methodologies for Maritime Transportation (Intelligent Systems Reference Library,, 2018)
This book is one of very few in the maritime literature that solely focus on the latest developments in information technology (IT) methodologies in this field. It provides the reader with a concise overview of how IT can truly improve the efficacy of operations in the maritime industry. It consists of seven chapters that address a range of topics related to the synergy between Computer Science and Maritime Science. Specifically, Chapters 1 and 2 explore two important problems in maritime logistics pertaining to quayside operational planning, while Chapters 3 and 4 focus on maritime routing methodologies. Chapters 5 and 6 present decision-making support systems for safe shipping and port security. Last, Chapter 7 presents simulation methodologies for modeling maritime traffic. The intended readership of the book spans both an academic audience and professionals in the areas of Operational Research, Transportation Science, and Maritime Science interested in applying IT methodologies in their areas of expertise.